Vinayak Damodar Savarkar’s Essentials of Hindutva: A Study of Its Philosophical Elements to Hindu Nationalism - Nguyen Tran Tien (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In the early twentieth-century, the concepts of Hindutva, Samyavada or Nationalism and national identity, reconstructed amid currents of globalization and neo-colonialism. During this period, the calls for an independent India reached its height. While, Mohandas Gandhi and Jawaharlal Nehru believed modern India’s strength depended on incorporating the solidarities of all Indians as they stood on the precipice of the postcolonial age, Veer Vinayak Damodar Savarkar (1883-1966), an ethnocentric nationalist, held that a strong Hindu nation was the only way to guarantee India’s security against the Muslim other and the British imperialism. Being the philosopher of Hindutva, Savarkar represented the ethno-nationalistic component to Hindu nationalism and looked to cultural motifs in order to unify the “true” people of India. He, therefore, wrote glorified histories of India and its millennia-old cultural traditions in his essays. This article analyzes and historically contextualizes the timing and the rhetorical style of V. D. Savarkar’s infamous extended essay “Essentials of Hindutva”. Received 9thDecember 2020; Revised 2nd March 2021; Accepted 20th March 2021